Unfolding The User Experience: A Comprehensive User Experience Framework For Foldable Smartphones - Liu, Yankuan; Dong, Lili; Rau, Pei-Luen Patrick (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This study presents a comprehensive framework for understanding User Experience (UX) in foldable smartphones, a rapidly emerging mobile technology category. Through product research, user studies, and expert evaluations, this research identifies three core elements: the hinge, the user, and the folding-state interface. The framework emphasizes the hinge’s crucial role in maintaining screen continuity, enhancing portability, and ensuring user comfort during folding operations. Ergonomic compatibility and psychological acceptability are identified as essential user factors, while state consistency, intuitive compatibility, proper feedback, and exclusive features constitute vital interface elements. An exploratory case study examining the impact of hand size on UX revealed significant differences in pressure application and fatigue levels between users with different hand sizes, highlighting the importance of ergonomic considerations in design. This framework provides a foundation for future development in foldable smartphones, aiming to improve product attractiveness by systematically addressing specific user requirements and experiences.